Dictionary of Contemporary Religion in The Western World - Christopher H. Partridge (ed.) (Christopher Hugh) 1961-; Douglas R. Groothuis 1957- (England InterVarsity Press, 2002)
"During the past century, the religious landscape of the Western world has changed dramatically. All of us now live in multi-faith societies, in which established religions co-exist with new and alternative spiritualities. The internet and the rapid development of communication technologies have increased our awareness and knowledge of other cultures and communities." "Effective Christian ministry thus demands a basic grasp of the beliefs and practices of other faiths. Drawing together the best in conservative Christian scholarship, this dictionary provides concise discussion and analysis of contemporary religions in the context of modern and postmodern culture." "The volume has a bipartite structure: Part One consists of introductory articles dealing with general religious and cultural issues; Part Two contains articles on the principal religions and new religious movements found in the West." "An accessible work of reference, the Dictionary of Contemporary Religion in the Western World will be an indispensable tool for scholars and students, teachers and ministers, Christian workers, and anyone who is seeking an informed understanding of today's religious plurality."--Jacket
Blasphemy -- to -- Zorastrianism
Keywords: Religions (3GdCOjGfs; General -- Dictionaries